Faktor-Faktor Penyebab Terjadinya Kejahatan Pencurian Berulang - Ikhwanuddin Harahap, Rizki Handayani Harahap & Fatahuddin Aziz Siregar & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
Along with the development of times, crime also develops, one of which is the crime of theft. Repeated theft crimes in Class IIB Lapas Padangsidimpuan, the returns of convicts who repeat the crime after being released from their criminal sentence or prisoners who return to be resident of the correctional facility. The occurrence of the repeated theft crime phenomenon result in a person being subject to sanctions for their actions. The existence of repeated theft crimes creates no deterrent in commiting crimes and repeats the crime. The occurrence of the repeated theft crime phenomenon, of course there are factors that cause the occurrence of repeated theft crimes in Class IIB Prison in Padangsidimpuan City. The problem in this research is what are the factors causing the occurrence of recurrent theft crimes in Padangsidimpuan Class IIB Prison and how the jinayah fiqh review on recurring theft. The purpose of this study is to find out what are the factors that cause the occurrence of repeated theft crimes in Padangsidimpuan Class IIB Prison and to find out how the jinayah fiqh review on recurring theft. This type of research is field research using a sociological juridical approach. The approach of this research is by means of interviews and documentation related to the factors of the occurrence of repeated theft crimes. As for what the researchers examined were officers and convicts of repeated theft at the Class IIB Prison in Padangsidimpuan City. The result of this study are the factors that cause the occurrence of repeated thefts in the Class IIB Prison in Padangsidimpuan City are economic factors, individual factors, factors of lack of religious knowledge. In the jinayah fiqh review of repeated theft crimes, this is in accordance whith hadis narrated by Abu Hurairah, namely the first theft is punishable by cutting off his right hand, second theft of cutting his left leg, third theft of cutting off his left hand, and theft of four cutting off his right leg. Then the Hanabilah and Hanafiyah scholars argued that the first theft was punished by cutting off the right hand, the second theft by cutting off the left leg, the third and fourth theft being punished by ta’zir. Penalties in the criminal code are similar to jinnayah fiqh, which is equally burdensome in penalties for repeat theft perpetratos.